The succession of One Day Surgery with Breast Cancer Home Recovery Program by the National Cancer Institute (ODS BHR NCI) during the COVID-19 pandemic in Thailand - Chayanoot Rattadilok; Napaphat Poprom; Vipavee Niyomnaitham; Oradee Phadhana-anake; Jirawadee Ruamjaroenchai; Napat Saigosoom; Wimonporn Papathe; Suttida Thuranutch; Araya Chanwet (Surgery Open Science)
Background: Breast cancer is the most common cancer among women. In response to the need to hospital stays and minimize waiting time for surgery, particularly during the COVID-19 pandemic, the National Cancer Institute developed the One Day Surgery with Breast cancer Home Recovery program (ODS BHR NCI). The aim of study is to assess the success rate of breast cancer surgeries conducted through this program and to evaluate the incidence of complications. Method: The cohort study includes all breast cancer patients who underwent surgery through the ODS BHR NCI program between August 2021 to November 2023. Eligible participants were under 70 years of age. The patients received comprehensive care and education from a multidisciplinary team, adhering to the program's guidelines. Their postoperative outcomes were monitored on the 1st, 3rd, and 5th days following discharge. Result: A total of 206 patients participated in the ODS BHR NCI program during the COVID-19 pandemic in Thailand. The mean age and BMI were 54.21 ± 9.74 years and 24.18 ± 4.02, respectively. The success rate was 99.02 %, with only one case involving a serious complication. Minor complications were reported in 20 cases, including anesthesia-related issues and minor surgical complications. Notably, no patients were diagnosed with COVID-19 following their surgery. Conclusion: Breast cancer surgeries performed under the ODS BHR NCI program achieved a high success rate. The development of pre-, intra-, and post-operative care protocols, alongside comprehensive patient education, has potential to reduce complications and provide an effective model for extending systemic care to a wider range of patients.